Social costs of illicit financial flows in low- and middle-income countries: the case of infant vaccination coverage - Ortega-Aguaza, Bienvenido; Sanjuán-Solís, Jesús Carlos; Casquero-Tomás, Antonio (Oxford University Press, 2017)
The liberalization of capital flows is generally associated with prospects of higher growth. However, in developing countries, opening the capital account may also facilitate the flow of capital out of the country through illicit financial flows (IFFs). Given that IFFs drain the scarce public resources available to finance the provision of public goods and services, the extent of illicit capital flows from developing countries is serious cause for concern. In this context, as a first step in analysing the social costs of IFFs in developing countries, this article studied the relationship between IFFs and infant immunization coverage rates. Data for 56 low- and middle-income countries for the period 2002–13 were used in the empirical analysis. The main result was that the relative level of IFFs to total trade negatively impacted vaccination coverage but only in the case of countries with very high levels of perceived corruption. In this case, the total effect of an annual 1 p.p. increase in the ratio of IFFs to total trade was to reduce the level of vaccination coverage rates over the coming years by 0.19 p.p. Given that there was an annual average of 18 million infants in this cluster of 25 countries, this result suggests that at least 34 000 children may not receive this basic health care intervention in the future as a consequence of this increase in IFFs in any particular year.
Keywords: Vacunación infantil - Costes; Illicit financial flows; Infant vaccination coverage; Low- and middle-income countries; Panel data analysis